Working out of the estimation procedure of brake properties of the car at diagnostic station - Шаша, И.К.; Гаркавцев, Е.И.; Фесенко, Г.И.; Цебрюк, И.В. (Eastern-European Journal of Enterprise Technologies, 2010)
The article is devoted to the current problem concerning traffic accidents’ decrease, the reason of which is loss of durability by vehicles. Research method of front wheel drive vehicle’s brake characteristics on a rolling test bench of a movable diagnostic station is elaborated.